(untitled) (Medical Forum Monthly, 2024)
Objective: To find out whether obesity is associated with low grade systemic inflammation as measured by serum c-reactive proteins (CRP) levels. Study Design: Cooperative Observational Study Place and Duration of Study: This was conducted in the department of Physiology BMSI, JPMC with the collaboration of gynecology & obstetric department of JPMC Karachi from October 2008 to May 2009. Materials and Methods: This study includes thirty obese pregnant women and thirty normal weight pregnant women as a control group of similar age, sex, height and gestational age. Subjects were randomly selected from gynae OPD of JPMC Karachi. Results: The mean values of C – reactive protein concentration was higher in obese pregnant women as compared with control group (4.3±0.16 mg/L vs 9.0±12 mg/L). It showed statistically significant positive correlation with body mass index (BMI). Conclusion: Higher BMI was associated with higher C-Reactive proteins concentration. These findings suggest a state of low-grade systemic inflammation in obese pregnant women.